Mapping Global Research Trends in Green Business for Sustainable Development: A Bibliometric Analysis (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The concept of green business performance has been an interesting topic for research among well-known scholars. Green business has become crucial for advancing sustainability and fostering innovation. Green business performance has become the global requirement due to the recent economic disaster, and green measures have been considered the leading solution for it. This study aims to explore how sustainability intersects with strategic business practices, offering actionable insights for aligning environmental sustainability with economic growth. To find worldwide research trends, bibliometric analysis was performed using R studio and VOSviewer software on 3007 scientific publications from Scopus from 2021 to 2024. Bibliometric analysis uses key words to enable the study of specific details, within the main topics of research, within a domain, and relationships at the micro-level. These methods facilitated an in-depth exploration of the evolution and impact of green business for sustainability. This study bridges existing gaps by providing actionable insights into how green business drive sustainable development, offering value to researchers, policymakers, and business leaders seeking to integrate environmental sustainability with economic growth.